Unraveling the Mode of Action of Cordyceps fumosorosea: Potential Biocontrol Agent against Plutella xylostella (Lepidoptera: Plutellidae) - Yanyuan Lei; Abid Hussain; Zhaoying Guan; Desen Wang; Waqar Jaleel; Lihua Lyu; Yurong He (Insects, 2021)
The entomopathogenic fungus, Cordyceps fumosorosea is a potential eco-friendly biocontrol agent. The present study revealed the entire course of infection of P. xylostella by C. fumosorosea with particular reference to cuticular penetration. Comparative studies on the infection of Plutella xylostella larvae by two strains of C. fumosorosea with different pathogenicity were carried out using light, scanning, and transmission electron microscopy. We found that C. fumosorosea tended to adhere to the cuticle surfaces containing protrusions. Although conidia of the lower pathogenic strain IFCF-D58 germinated, they failed to penetrate and complete the development cycle. In contrast, the higher pathogenic strain IFCF01 began to germinate within 4 h and attached to the cuticle by a thin mucilaginous matrix within 8 h post-inoculation. After 24 h post-inoculation, germ tubes and penetrating hyphae reached the cuticular epidermis and began to enter the haemocoel. Within 36 h post-inoculation, the hyphal bodies colonized the body cavity. Hyphae penetrated from inside to outside of the body after 48 h and sporulated the cadavers. After 72 h post-inoculation, numerous conidia emerged and the mycelial covered the entire cuticular surface. The two strains showed similarities in terms of conidial size and germination rate. However, IFCF-D58 exhibited significantly fewer appressoria and longer penetrating hyphae compared to the more infective IFCF01 on all surface topographies. The current pathogen invasion sequence of events suggested that the aggressive growth and propagation along with rapid and massive in vivo production of blastospores facilitate the conidia of IFCF01 to quickly overcome the diamondback moth’s defense mechanism.